2018
DOI: 10.1016/j.rboe.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between the neutrophil/lymphocyte ratio and bilaterality in patients with coxarthrosis?

Abstract: ObjectiveThe objective of this study was to evaluate the relationship between the neutrophil/lymphocyte ratio and the presence of signs of arthrosis in both hips in patients followed at this medical center.MethodsThis was a cross-sectional, retrospective study through the analysis of medical records and database review of patients over 18 years of age with hip arthrosis, followed at the outpatient clinic of this hospital.ResultsRegarding the analysis of the Mann–Whitney test to correlate the neutrophil/lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Only one study has investigated the levels of NLR in HOA. Barbosa et al found that NLR values were higher in unilateral coxarthrosis than that in the bilateral group 17 . Many studies investigated NLR levels in knee OA in the literature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Only one study has investigated the levels of NLR in HOA. Barbosa et al found that NLR values were higher in unilateral coxarthrosis than that in the bilateral group 17 . Many studies investigated NLR levels in knee OA in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…The relationship between the presence of HOA and inflammatory parameters has not yet been demonstrated 17 . In this study, the relationship between the presence of HOA and NLR, NMR, PLR, and MLR, which are indicators of inflammation, was evaluated.…”
Section: Discussionmentioning
confidence: 98%